Fishermen's Adaptation Strategy for Developing Beach Tourism 9 in Bringsang Village, Gili Genting District, Sumenep Regency - fawaid asad (MAP Observer: Jurnal Penelitian Administrasi Publik, 2026)
This study examines fishermen's adaptation strategies to the development of the 9 Beach tourist attraction in Bringsang Village, Gili Genting District, Sumenep Regency. The development of the 9 Beach tourist attraction, as part of a government ecotourism project, has had social, economic, and cultural impacts on the local community, particularly fishermen and coastal residents. This development program was accompanied by land acquisition, which has generated both pros and cons within the community. Some residents supported the tourism development because it was seen as capable of boosting regional economic growth, creating jobs, and improving infrastructure. However, others opposed it, fearing the loss of land, livelihoods, and social and cultural identities that had been passed down through generations.This study employed a qualitative research method with a case study approach. Data collection techniques included unstructured interviews, observation, and documentation studies. The analysis utilized social movement theory and Sidney Tarrow's theory of resistance to the land acquisition policy. The results showed that the community employed various adaptation and resistance strategies, including the formation of community groups against eviction, social mobilization, collaboration with legal aid institutions, and the framing of the issue through slogans and social media. This movement successfully delayed the land acquisition process for several years. This study concludes that tourism development must involve active community participation to ensure development proceeds without damaging local culture, the environment, and the livelihoods of coastal communities.